2009
DOI: 10.1093/molbev/msp239
|View full text |Cite
|
Sign up to set email alerts
|

Infrequent Transitions between Saline and Fresh Waters in One of the Most Abundant Microbial Lineages (SAR11)

Abstract: The aquatic bacterial group SAR11 is one of the most abundant organisms on Earth, with an estimated global population size of 2.4 Â 10 28 cells in the oceans. Members of SAR11 have also been detected in brackish and fresh waters, but the evolutionary relationships between the species present in the different environments have been ambiguous. In particular, it was not clear how frequently this lineage has crossed the saline-freshwater boundary during its evolutionary diversification. Due to the huge population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
83
3
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(96 citation statements)
references
References 40 publications
8
83
3
2
Order By: Relevance
“…Although ancient, colonization of freshwater sediment occurred more recently than for saline sediments in a first transition and subsequent diversification events that gave rise to all freshwater MCG-IL (Figure 6). Overall, and in agreement with other microbial lineages (Logares et al, 2009(Logares et al, , 2010), a few environmental transition events (that is, switch from a freshwater ancestor to a saline descendant and vice versa) seemed to have occurred during the diversification of MCG. This result may explain why freshwater and saline sediments harbored evolutionary distinct communities of MCG.…”
Section: Evolutionary Relationships Between Freshwater and Marine Mcgsupporting
confidence: 85%
“…Although ancient, colonization of freshwater sediment occurred more recently than for saline sediments in a first transition and subsequent diversification events that gave rise to all freshwater MCG-IL (Figure 6). Overall, and in agreement with other microbial lineages (Logares et al, 2009(Logares et al, , 2010), a few environmental transition events (that is, switch from a freshwater ancestor to a saline descendant and vice versa) seemed to have occurred during the diversification of MCG. This result may explain why freshwater and saline sediments harbored evolutionary distinct communities of MCG.…”
Section: Evolutionary Relationships Between Freshwater and Marine Mcgsupporting
confidence: 85%
“…hyp -oxia) or a more recent ecological diversification of LD12 that is not detected in the rather slowly evolving 16S rRNA gene. Previous phylogenetic analyses of LD12 from a global 16S rRNA database do support microdiversification and hence the existence of ecologically and genetically diversified LD12 populations (Logares et al 2010). A more recent phylogeographic analysis suggests that such subclusters (supported bootstrap values > 50%) were typically restricted to single lakes, but several clusters could occasionally also be detected within a single system (Lake Zürich; Salcher et al 2011a).…”
Section: Discussionmentioning
confidence: 95%
“…(Logares et al 2010). SAR11 bacteria are often a numerically dominant component of prokaryotic communities in marine waters (Morris et al 2002), and there is one lineage of SAR11 that is found mainly in brackish waters (Logares et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Marine organisms are isotonic or hypotonic, while freshwater ones are hypertonic. Both physiology and the cost of osmoregulation make the marine-freshwater boundary an insurmountable barrier for many bacteria (Logares et al 2010). As a result, there is almost no overlap in the community composition of marine and freshwater species.…”
mentioning
confidence: 99%